A Problem‐Solving Intervention for Hospice Family Caregivers: A Randomized Clinical Trial. Issue 7 (4th April 2019) - Demiris, George; Oliver, Debra Parker; Washington, Karla; Pike, Kenneth
Abstract : OBJECTIVES: Family caregivers of hospice patients have multiple needs as they try to cope during a stressful time. Translatable interventions effective in improving caregiver outcomes are greatly needed. Our objective was to assess the impact of a problem‐solving intervention (called Problem‐Solving Intervention to Support Caregivers in End‐of‐Life Care Settings [PISCES]) to support hospice caregivers on caregiver quality of life and anxiety, and compare its effectiveness delivered face to face and via videoconferencing. DESIGN: In this 4‐year randomized clinical trial, caregivers were randomly assigned to a group receiving standard care with added "friendly calls" (attention control [AC] group), a group receiving standard care and PISCES delivered face to face (F2F), or a group receiving standard care and PISCES delivered via videoconferencing (VC). SETTING: Home hospice. PARTICIPANTS: A total of 514 caregivers participated (172 in AC, 171 in F2F, and 171 in VC). Caregivers were predominantly female (75%); mean age was 60.3 years. INTERVENTION: PISCES includes a structured curriculum delivered in three sessions and motivates caregivers to adopt a positive attitude, define problems by obtaining facts, set goals, and generate and evaluate solutions. MEASUREMENTS: Quality of life was measured by the Caregiver Quality of Life Index‐Revised; anxiety was measured by the Generalized Anxiety Disorder 7‐Item. Other measures included the Caregiver Reaction Assessment scale, demographic data, and an exit interview. RESULTS: Compared with AC, caregivers in the F2F condition had postintervention reduced anxiety (−1.31 [95% confidence interval [CI] = −2.11 to .50]; p  = .004) and improved social (.57 [95% CI = .19‐.95]; p  = .01), financial (.57 [95% CI = .21‐.93]; p  = .004), and physical quality of life (.53 [95% CI = .19‐.87]; p  = .01). There were no differences in caregivers in the VC condition compared with the AC condition. CONCLUSION: The PISCES intervention improves caregiver outcomes and is effective when delivered in person. How to integrate technology to reduce the intervention delivery cost warrants further investigation. Abstract : See related editorial byJohn Cagle .